2020
DOI: 10.1521/jscp.2020.39.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Unit Cohesion and Social Support as Protective Factors Against Suicide Risk and Depression Among National Guard Service Members

Abstract: Introduction: Suicide and depression continue to be pervasive problems across military populations, including within the National Guard. Existing literature highlights the protective effects of social support and unit cohesion for both suicide risk and depression, yet to our knowledge, these associations have never been confirmed in National Guard populations. Thus, the aim of this study was to investigate the impacts of social support resources (i.e., general social support and unit cohesion) on depression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Third, the unit of analysis for the unit cohesion constructs was on the individual level, as reported by an informant. More recent research is needed examining unit cohesion from the perspective of the informant and comparing the individual-and unit-level cohesion factors related to STBs (Campbells-Sills et al, 2020;Rugo et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the unit of analysis for the unit cohesion constructs was on the individual level, as reported by an informant. More recent research is needed examining unit cohesion from the perspective of the informant and comparing the individual-and unit-level cohesion factors related to STBs (Campbells-Sills et al, 2020;Rugo et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…Military personnel who feel valued and appreciated by their colleagues experience less suicidal ideation (Bryan & Hernandez, 2013). More recently, Rugo et al (2020) found higher levels of perceived unit cohesion predicted lower levels of depression and suicidal ideation at the individual level and not the unit level in a National Guard Sample. Campbell-Sills et al (2020) reported the important influence of horizontal (peer bonds) and vertical unit cohesion (leadership and subordinates bonds) as a buffer of stress and symptoms of PTSD, depression, and suicidal ideation (Campbell-Sills et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Team cohesion is not only associated with perceived differences among team members, it is also related to social support (Urien et al , 2017). A positive relationship is suggested between team cohesion and social support (Rugo et al , 2020), hence a lower level of cohesion may be associated with lower levels of social support amongst team members.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Critically, this protective effect can be derived from the unit to which a service member is assigned. For example, service members are significantly less likely to report suicide ideation when they are assigned to units with people who report a high level of perceived social support [ 26 ]. Trauma-exposed service members also report less severe emotional distress when assigned to units with people who report experiencing positive emotions more frequently [ 27 ].…”
Section: The Airman’s Edge Peer-to-peer (P2p) Programmentioning
confidence: 99%